Physician Experiences and Understanding of Genomic Sequencing in Oncology. Issue 1 (24th August 2017) - Weipert, Caroline M.; Ryan, Kerry A.; Everett, Jessica N.; Yashar, Beverly M.; Chinnaiyan, Arul M.; Scott Roberts, J.; De Vries, Raymond; Zikmund‐Fisher, Brian J.; Raymond, Victoria M.
Abstract: The amount of information produced by genomic sequencing is vast, technically complicated, and can be difficult to interpret. Appropriately tailoring genomic information for non‐geneticists is an essential next step in the clinical use of genomic sequencing. To initiate development of a framework for genomic results communication, we conducted eighteen qualitative interviews with oncologists who had referred adult cancer patients to a matched tumor‐normal tissue genomic sequencing study. In our qualitative analysis, we found varied levels of clinician knowledge relating to sequencing technology, the scope of the tumor genomic sequencing study, and incidental germline findings. Clinicians expressed a perceived need for more genetics education. Additionally, they had a variety of suggestions for improving results reports and possible resources to aid in results interpretation. Most clinicians felt genetic counselors were needed when incidental germline findings were identified. Our research suggests that more consistent genetics education is imperative in ensuring the proper utilization of genomic sequencing in cancer care. Clinician suggestions for results interpretation resources and results report modifications could be used to improve communication. Clinicians' perceived need to involve genetic counselors when incidental germline findings were found suggests genetic specialists could play a critical role in ensuring patients receive appropriate follow‐up.